2010
DOI: 10.1002/jrs.2810
|View full text |Cite
|
Sign up to set email alerts
|

Structure elucidation of fluorescent H1 antihistamines by ultraviolet resonance Raman spectroscopy: solvent structures of tripelennamine and mepyramine

Abstract: Ultraviolet Resonance Raman (UVRR) spectroscopy -a Raman technique that combines high sensitivity with high selectivity and does not suffer from background fluorescence -is applied to the fluorescent H 1 antihistamines tripelennamine (TRP) and mepyramine (MEP) in aqueous solution to elucidate their molecular structure as a function of pH. In a previous investigation of these compounds (C. Tardioli, G. Gooijer G. van der Zwan, J. Phys. Chem. B, 113, (2009), 6949), the presence of gauche conformers caused by int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 18 publications
(35 reference statements)
2
10
0
Order By: Relevance
“…At pH 9 only 50% of the molecules will be protonated at the tail (pK a = 8.9). 2,3 Antihistamine/HSA Complex and K a Evaluation. The pH influence on the binding of TRP and MEP to HSA was first investigated by means of UV absorption spectroscopy.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…At pH 9 only 50% of the molecules will be protonated at the tail (pK a = 8.9). 2,3 Antihistamine/HSA Complex and K a Evaluation. The pH influence on the binding of TRP and MEP to HSA was first investigated by means of UV absorption spectroscopy.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…We recently made use of the same technique to successfully investigate the solution conformation of TRP and MEP. 2 We showed that there is a definite influence of the protonated ethylamino chain on the chemical and photophysical properties of these molecules. Most probably for TRP and MEP the HSA−ligand interaction is affected by their solution conformations, which in turn are dependent on the protonation state of the tail.…”
Section: ■ Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…carried out resonance Raman scattering with 239.5‐ and 245.9‐nm excitation wavelengths and a DFT theoretical analysis of the photodissociation dynamics of formanilide in S 3 state . Tardioli and co‐workers elucidated the structure of fluorescent H1 antihistamines by ultraviolet resonance Raman spectroscopy to learn more about the solution structures of tripelennamine and mepyramine . Wei et al .…”
Section: Resonance Raman Spectroscopymentioning
confidence: 99%